William H. Taft papers - Taft, William H. (William Howard), 1857-1930.; Carpenter, Fred W., 1873 or 4-1957; Taft, Alphonso, 1810-1891.; Taft, Louise Maria Torrey, 1827-1907.; Taft, Helen Herron, 1861-1943.; Torrey, Delia C.
Correspondence including 219 volumes of letterpress books (1890-1920), speeches and addresses, presidential and judicial files, legal papers and notebooks, family papers and letters, business and estate papers, engagement calendars, guest lists, scrapbooks, clippings, printed matter, memorabilia, and photographs documenting Taft's career as U.S. solicitor general (1890-1892), U.S. circuit court judge (1892-1900), president of the U.S. Philippine Commission (1900-1901), governor of the Philippines (1901-1904), secretary of war in Theodore Roosevelt's cabinet (1904-1908), president of the United States (1909-1913), professor of constitutional law at Yale Law School (1913-1921), and chief justice of the U.S. Supreme Court. Also documents Taft's service as president of the American Bar Association (1913), president of the League to Enforce Peace (1915), and member and cochairman of the National War Labor Board (1918-1919).
Family members respresented include Taft's father, Alphonso Taft, U.S. secretary of war (1876), attorney general (1876-1877), and minister to Austria-Hungary (1882-1884) and to Russia (1884-1885); his mother, Louise Maria Torrey Taft, civic leader and advocate of the kindergarten movement; his wife, Helen Herron Taft; and his aunt, feminist Delia C. Torrey. Correspondence among these and other Taft family members reflects social and intellectual life in the United States during the late 19th and early 20th centuries. Also includes desk diaries and other papers of President Taft's private secretary, Fred W. Carpenter.
Correspondents include Nelson W. Aldrich, Chester Alan Arthur, Robert Bacon, Richard Achilles Ballinger, Albert Jeremiah Beveridge, Mabel Thorp Boardman, Joseph L. Bristow, Viscount James Bryce, Nicholas Murray Butler, Archibald Willingham Butt, Joseph Gurney Cannon, George B. Cortelyou, Charles Curtis, John A. Dix, Charles W. Fairbanks, John Hays Hammond, Myron T. Herrick, Charles Evans Hughes, Robert Underwood Johnson, Walter H. Johnson, Frank B. Kellogg, Philander C. Knox, Robert Todd Lincoln, Henry Cabot Lodge, William H. Moody, Francis G. Newlands, Charles Dyer Norton, John J. Pershing, Gifford Pinchot, Whitelaw Reid, Theodore Roosevelt, Elihu Root, J. S. Sherman, Henry Lewis Stimson, Nathan Straus, Oscar S. Straus, Robert A. Taft, Willis Van Devanter, Booker T. Washington, Edward Douglass White, George W. Wickersham, James Wilson, Woodrow Wilson, and Luke E. Wright.
Microfilm edition available for series 1-26
Microfilm produced from originals in the Manuscript Division
President of the United States and chief justice of the Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Six volume index published by the Library of Congress in 1972 available in the Library of Congress Manuscript Reading Room. Cataloged in record 70608096.
Keywords: Aldrich, Nelson W. -- 1841-1915 -- Correspondence; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Bacon, Robert, -- 1860-1919 -- Correspondence; Ballinger, Richard Achilles, -- 1858-1922 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Boardman, Mabel Thorp, -- 1860-1946 -- Correspondence; Bristow, Joseph L. -- 1861-1944 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Butt, Archibald Willingham, -- 1866-1912 -- Correspondence; Cannon, Joseph Gurney, -- 1836-1926 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Curtis, Charles, -- 1860-1936 -- Correspondence; Dix, John A. -- 1860-1928 -- Correspondence; Fairbanks, Charles W. -- 1852-1918 -- Correspondence; Hammond, John Hays, -- 1855-1936 -- Correspondence; Herrick, Myron T. -- 1854-1929 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Johnson, Robert Underwood, -- 1853-1937 -- Correspondence; Johnson, Walter H., -- b. 1848 -- Correspondence; Kellogg, Frank B. -- 1856-1937 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Moody, William H. -- 1853-1917 -- Correspondence; Newlands, Francis G. -- 1848-1917 -- Correspondence; Norton, Charles Dyer, -- 1871-1922 -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Sherman, J. S. -- 1855-1912 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Straus, Nathan, -- 1848-1931 -- Correspondence; Straus, Oscar S. -- 1850-1926 -- Correspondence; Taft, Robert A. -- 1889-1953 -- Correspondence; Van Devanter, Willis, -- 1859-1941 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; White, Edward Douglass, -- 1845-1921 -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Wilson, James, -- 1835-1920 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Wright, Luke E. -- 1846-1922 -- Correspondence; Taft family -- Correspondence; American Bar Association; League to Enforce Peace (U.S.); United States. -- Dept. of Justice. -- Office of the Attorney General; United States. -- National War Labor Board (1918-1919); United States. -- Philippine Commission (1900-1916); United States. -- Solicitor General; United States. -- Supreme Court; United States. -- War Dept; Yale Law School -- Faculty; Circuit courts -- United States; Constitutional law -- United States; Constitutional law -- Study and teaching; Diplomatic and consular service, American -- Austria; Diplomatic and consular service, American -- Russia; Feminism